Seismic Performance and Configuration Assessment of Deficient Steel Frames Equipped with Buckling Restrained Braces - Mazen Shrif; Zaid Al-Sadoon; Ahed Habib (Journal of Rehabilitation in Civil Engineering)
Integrating Buckling Restrained Braces (BRBs) into seismic-resistant structural frameworks presents a sophisticated approach to improving seismic performance. Despite the breadth of research conducted in this area, a noticeable gap persists in comprehending the optimal deployment of BRBs within steel frames that exhibit deficiencies to attain maximal structural efficiency and resilience in seismic events. To address this gap, the present study examines the most efficacious configurations of BRBs. Employing a methodological framework that encompasses the design, modeling, and analysis of twenty-four steel frames demonstrating deficiencies and outfitted with BRBs in varied configurations, this investigation utilizes nonlinear response history analysis as its core analytical tool. This comparative analysis examines eight distinct BRB configurations against a reference scenario devoid of BRBs to identify which most effectively augments seismic resistance. The outcomes derived from the nonlinear response history analysis underscore the pronounced influence of BRB configurations and geometrical variations on critical parameters, including frame weight, base shear, overturning moment, and lateral displacement at the story level. Case C2 was identified as the optimal configuration due to its balanced combination of enhanced performance and weight reduction, making it a reasonable choice for structural efficiency.